Evaluation of Employee Engagement Level in Improving Productivity and Retention in the Company - Adriyanto, Agus (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to evaluate the critical role of employee engagement in enhancing productivity, retention, and organizational sustainability. It investigates how engagement influences individual and team performance, explores contextual factors affecting engagement, and proposes strategies to address challenges in maintaining high levels of employee engagement. The study employs a Systematic Literature Review approach, synthesizing qualitative insights from diverse organizational contexts. It integrates theoretical frameworks, particularly the Job Demands-Resources Model, to analyze the interplay between engagement, job demands, and managerial resources. Secondary data from reputable academic sources are systematically reviewed to uncover patterns and insights into employee engagement dynamics. The findings reveal that employee engagement directly enhances motivation, creativity, and innovation, fostering higher productivity and reducing turnover. Engagement is influenced by both internal factors (recognition, career development opportunities, and managerial support) and external factors (work models, organizational culture, and work-life balance policies). Additionally, the study highlights challenges such as workload pressures, generational differences, and the complexities of remote and hybrid work environments. Practical strategies, such as recognition programs, flexible work policies, and leveraging engagement analytics, are critical to sustaining engagement and organizational success. Practically, this research offers evidence-based recommendations for organizations to design adaptive engagement strategies that enhance productivity, reduce turnover, and support long-term sustainability. The study also contributes to academic discourse by expanding the theoretical understanding of engagement within contemporary work contexts. Future research should address longitudinal analyses and explore emerging factors like technology and generational shifts to refine engagement strategies further.